Barcoded Hybrids of Extracellular Vesicles and Lipid Nanoparticles for Multiplexed Analysis of Tissue Distribution - Alena Ivanova; Renata Chalupska; Ana Filipa Louro; Mike Firth; Hernán González‐King Garibotti; Leif Hultin; Franziska Kohl; Elisa Lázaro‐Ibáñez; Julia Lindgren; Gentian Musa; Erik Oude Blenke; Andreia M. Silva; et al. (Advanced Science)
Abstract Targeted delivery of therapeutic agents is a persistent challenge in modern medicine. Recent efforts in this area have highlighted the utility of extracellular vesicles (EVs) as drug carriers, given that they naturally occur in bloodstream and tissues, and can be loaded with a wide range of therapeutic molecules. However, biodistribution and tissue tropism of EVs remain difficult to study systematically. Here, a multiplexed approach is developed for simultaneous tracking of EVs from various cell lines within a single in vivo experiment. EVs are used from 16 different cell lines, and through controlled fusion with lipid nanoparticles (LNPs) carrying single‐stranded DNA barcodes, uniquely barcoded hybrid EV particle (hEV) library is generated. These hEVs are combined for a multiplexed in vivo biodistribution profiling in mice, and discovered that HAP1‐derived hEVs demonstrated lung tropism, suggesting that these hEVs may be used for targeted drug delivery into lung tissue. To examine this possibility further, it is shown that HAP1 hEV loaded with Cre mRNA displayed functional delivery to the lungs. Overall, the barcoded hEV technology enables rapid profiling of biodistribution across EV cell sources, which is poised to improve throughput and extent of EV studies, while reducing the number of animals required for research.